Dietary supplementation of black soldier fly (Hermetica illucens) meal modulates gut microbiota, innate immune response and health status of marron (Cherax cainii, Austin 2002) fed poultry-by-product and fishmeal based diets - Foysal, Md Javed; Fotedar, Ravi; Tay, Chin-Yen; Gupta, Sanjay Kumar (PEERJ INC, 2019)
The present study aimed to evaluate the dietary supplementary effects of black soldier fly (Hermetia illucens) (BSF) meal on the bacterial communities in the distal gut, immune response and growth of freshwater crayfish, marron (Cherax cainii) fed poultry-by-product meal (PBM) as an alternative protein source to fish meal (FM). A total of 64 marron were randomly distributed into 16 different tanks with a density of four marron per tank. After acclimation, a 60-days feeding trial was conducted on marron fed isonitrogenouts and isocalorific diets containing protein source from FM, PBM, and a combination of FM + BSF and PBM + BSF. At the end of the trial, weight gain and growth of marron were found independent of any dietary treatment, however, the two diets supplemented with BSF significantly (P < 0.05) enhanced haemolymph osmolality, lysozyme activity, total haemocyte counts, and protein and energy contents in the tail muscle. In addition, the analysis of microbiota and its predicted metabolic pathways via 16s rRNA revealed a significantly (P < 0.05) higher bacterial activity and gene function correlated to biosynthesis of protein, energy and secondary metabolites in PBM + BSF than other dietary groups. Diets FM + BSF and PBM + BSF were seen to be associated with an up-regulation of cytokine genes in the intestinal tissue of marron. Overall, PBM + BSF diet proved to be a superior diet in terms of improved health status, gut microbiota and up-regulated expression of cytokine genes for marron culture.